ANALISIS UJIAN NASIONAL MATEMATIKA SMP TAHUN 2014 SAMPAI 2017 DALAM TINJAUAN REPRESENTASI - Tundung Memolo (Universitas Muhammadiyah Semarang, 2017)
The purpose of this research is how to connect ideas and real experiences with mathematical representation and to analyze how big portion of representationin national junior mathematics exam year 2014 until 2017. Representation ingeneral become an important part for learning mathematics of teacher andstudent in playing explanation about ideas Mathematics that is closely relatedto real experience. Forms of representation include representations of sketches,graphs, diagrams, tables, drawings, or modeling. The results of representationon the national junior mathematics exam from 2014 to 2017 show that imagerepresentation has the largest share of 25% to 35%. While the representationsin the form of sketches, graphs, diagrams, tables, and modeling is still below10%. Total representation of the national exam number of 55% to 60% or about22-24 questions from 40 junior high school mathematics exam questions. Inother words, more than half of the national mathematics exam is presented inthe form of representation. Keywords: examinations, experienced, idea, national, representation